Implementation of Green Building Concept in High Rise Developments Through Appropriate Site Development (ASD) - Rezi Berliana Yasinta; Moch. Fariz Aditya; Fadhlan Shiddiq; Afifah Nur Agyta; Muhammad Rakha Ammar Farras; Muhammad Farid Alfawaz (Potensi: Jurnal Sipil Politeknik, 2025)
This study evaluates the implementation of green building criteria based on Appropriate Site Development (ASD) in the Jakarta State University Postgraduate Building. Using the Greenship assessment tool from the Indonesian Green Building Council (GBCI), the analysis focuses on ASD, which includes prerequisite and credit criteria. The building scored 8 out of 17 points, indicating partial compliance with ASD standards. Notable strengths include the Microclimate criterion, where all requirements were met. However, critical shortcomings were identified in Rainwater Management, which scored zero, reflecting unmet criteria. Similar issues were observed in Bicycle User Facilities and Site Landscape, which also received zero scores. Public transportation access was another area requiring improvement to support user mobility. Challenges in implementing the Green Building concept include limited land availability and high initial costs for environmentally friendly technologies. To address these issues, the study recommends enhancing land management by increasing green spaces, adding facilities for cyclists and eco-friendly vehicles, and involving the community in sustainability initiatives. These findings highlight areas for improvement and provide a framework for the sustainable development of educational buildings. This research aims to contribute to broader efforts in promoting green building practices within the education sector.